Employers' Civil Liability for Violation of Workers' Rights - Sukma, Sabrena (Vonis, 2025)
This research discusses the civil liability of employers for violations of workers' rights in labour relations. In labour practices, it is not uncommon to find violations of workers' normative rights, such as substandard wages, lack of social security, and unilateral termination of employment without compensation. This research aims to analyse the forms of civil liability that can be imposed on employers as well as dispute resolution mechanisms based on Indonesian civil law, particularly in the context of default and tort. The research method used is normative juridical with statutory approach and case study. The results show that employers who violate workers' rights can be held civilly liable, either through a lawsuit for compensation due to default on the employment agreement, or through the mechanism of tort claims. The enforcement of civil liability is expected to provide more effective legal protection for workers and encourage employers to comply with labour provisions.